ENSAIO PARA VOLTAR: PRODUÇÃO DE UM NEWSGAME PARA DISPOSITIVOS MÓVEIS - DIEGO EUBANK DE ALMEIDA (2022)
This is an applied research that aimed to produce a newsgame for mobile devices, which aimed to demonstrate implementation possibilities still little used for the dissemination of journalistic information via smart phones. The smartphone was chosen as a distribution platform for its technological and physical characteristics, as well as its participation with the individual in cyberspace in times of hybrid bodies and spaces. The game was developed according to studies focused on newsgames, which combines content from the multimedia report Ensaio para Voltar with the dynamics of simulation and question and answer. The conclusion was that the product of this research is characterized as a newsgame for smartphones. This game, however, can be further enriched with the implementation of the use of sensors available on mobile devices in order to increase the level of user interaction with the physical space in which they are.